2023
DOI: 10.3390/su15129306
|View full text |Cite
|
Sign up to set email alerts
|

Potential of an Area in Terms of Pro-Climate Solutions in a Land Consolidation Project

Abstract: Land consolidation plays an important role in promoting changes in agricultural land use and ensuring national food security. Moreover, it allows the land structure in rural areas to be built anew. By changing the spatial structure of the countryside, it is also possible to implement water and drainage measures as well as ecological and landscape measures aimed at improving farming conditions. At the same time, they have an impact on the climate. This study analysed the potential for the implementation of pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…Hao et al [86] reported that the NDVI reacted more strongly at higher temperatures. According to global forecasts, temperatures will continue to increase and precipitation will decrease, requiring preventative actions in Romania to deal with the negative implications of water shortages during the growing season [87]. Willows do not require strict cultivation conditions, according to researchers [88].…”
Section: Discussionmentioning
confidence: 99%
“…Hao et al [86] reported that the NDVI reacted more strongly at higher temperatures. According to global forecasts, temperatures will continue to increase and precipitation will decrease, requiring preventative actions in Romania to deal with the negative implications of water shortages during the growing season [87]. Willows do not require strict cultivation conditions, according to researchers [88].…”
Section: Discussionmentioning
confidence: 99%